The New York Times Assignment - King, John (Teaching History: A Journal of Methods, 2009)
Sometimes teachers develop favorite assignments that they use regularly in any number of their courses. 1 I have used and still use "The New York Times Assignment" in every history class I have taught since graduate school, whether at the college or high school level. This is probably the assignment I have changed the least, and it is certainly the most consistent assignment in my collection, because it continues both to be effective in accomplishing the three main objectives that I have for it, and because student feedback on the assignment, at all levels, has been consistently positive. "The New York Times Assignment" is a simple yet powerful tool that I use to help students accomplish the three major goals that I have set for all of my history courses: to help students make sense of what they are learning, to realize the importance of historical study, and to develop the critical thinking skills of the historian. The assignment is as follows: Find a current news article that is connected to something we have discussed in class. Cut out or print the article, write a one-paragraph summary of the article, and write a one-paragraph explanation of how the subject matter illustrates one of the topics or ideas we have discussed in our class. For some classes, I’ll add a third paragraph, explaining how the article illustrates as well one of the major themes of our course. As will become clear-or less clear-below, what J mean by "something we have discussed in class" is open to interpretation. Naturally, depending on the nature of the course and of the students, I modify the assignment to be more or less specific as needed. Otherwise, you now have the gist of it.